The Lexical and Contextual Meaning in Fajar Sadboy's Quotes - Vivi Novalia Sitinjak; Rifkha Sinambela; Dian Elizabeth Nababan; Yance Cerelina Sihotang; Grace Widya Hutagalung (Institut Agama Islam Negeri Palopo, 2023)
The goal of this study is to analyze the lexical and contextual significance of Fajar Sadboy's quotes. Researchers employed qualitative methods to carry out this study. Fajar Sadboy's utterances, obtained from web pages, served as the research's data source. Fajar Sadboy's quotes, which have lexical and contextual interpretations, serve as the study's primary source of data. This study used observation, lexical analysis, and contextual interpretation to collect the data. Fajar Sadboy's quotes were found online and recorded after being found, as well as their lexical and contextual meanings. The data is then examined using the meaning study. There are lexical meanings and contextual meanings based on the analysis of the quotes from Fajar Sadboy that was done for the research. Lexical meanings are dictionary translations of Indonesian and English words. The situation described in the quotes from Fajar Sadboy serves as the contextual meanings.